(untitled) (Materiali di Estetica. Terza serie, 2018)
In this paper I go over the thought of Alfredo Civita on some themes - psychoanalysis from a philosophical point of view, epistemological dualism between neurobiological sciences and psycho-behavioral sciences, the free will problem - through a dialogue that, started in university during the preparation of my thesis, continued until 2017 at the epistolary level and through a public correspondence in the context of my personal blog.